2013
DOI: 10.2141/jpsa.0120022
|View full text |Cite|
|
Sign up to set email alerts
|

Retraction: Estimation of the Relative Bioavailability of Several Zinc Sources for Broilers Fed a Conventional Corn-Soybean Meal Diet

Abstract: An experiment was conducted with 312 day-old male broiler chicks in grower phase (8-28d) to estimate the biological availability of four sources of zinc (Zn); zinc sulfate (ZnSO 4 ・H 2 O), two sources of zinc oxide (ZnO FG1 and ZnO FG2) and Bioplex Zn. Zinc sulfate was used as the standard in the bioavailability assay. Chicks were allotted randomly to 13 dietary treatments with 6 birds per replicate and 4 replicates per treatment, that included an unsupplemented corn-soybean meal basal diet (25.50 mg of Zn/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 32 publications
3
10
0
Order By: Relevance
“…These findings show that feed supplementation with Zn sulphate helps to improve the performance of broiler chickens, although significant difference compared to unsupplemented control birds was observed only in the average daily weight gain. Sahraei et al (2013) recorded higher weight gain in broilers fed similar dietary Zn concentrations from sulphate compared to control birds from day 22 to 28, which is partially consistent with our results. They also reported improvement of the feed conversion ratio in the birds supplemented with Zn sulphate and ZnPro compared to the control group, and no significant difference in the final body weight between treatments, which was not confirmed in our experiment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings show that feed supplementation with Zn sulphate helps to improve the performance of broiler chickens, although significant difference compared to unsupplemented control birds was observed only in the average daily weight gain. Sahraei et al (2013) recorded higher weight gain in broilers fed similar dietary Zn concentrations from sulphate compared to control birds from day 22 to 28, which is partially consistent with our results. They also reported improvement of the feed conversion ratio in the birds supplemented with Zn sulphate and ZnPro compared to the control group, and no significant difference in the final body weight between treatments, which was not confirmed in our experiment.…”
Section: Discussionsupporting
confidence: 92%
“…However, study results regarding the bioavailability of organic chelates remain controversial. Several studies show that organic Zn sources are more available to animals (Yenice et al 2015;Sahraei et al 2013;Yu et al 2010;Rupić et al 1997), contribute to elevation of Cu/Zn SOD activity in chicken liver ) and improve growth performance of broilers . In contrast, other results indicate that organic chelates are comparable to standard Zn sulphate (Cao et al 2000).…”
mentioning
confidence: 99%
“…High concentrations of Zn in poultry excreta due to their lower bioavailability cause environmental pollution and soil phytotoxicity when these excreta used as fertilizers and the high bioavailability of organic and nano-Zn will decrease Zn excretion [33]. Similarly, several studies reported that supplementation of organic minerals for broiler diets can improve the mineral uptake, enhance gain and reduce the excretion of minerals [34,35]. Nanoparticles revealed unique physical characteristics of transport and uptake that display higher absorption efficiencies when compared with the inorganic and organic Zn sources [36].…”
Section: Nutrient Retentionmentioning
confidence: 99%
“…e enrichment of poultry meat with functional ingredients and microelements is an added value and beneficial for human health. Sahraei et al [40] evaluated the bioavailability of four zinc sources (zinc sulphate, two sources of zinc oxide, and Bioplex Zn composed of organic zinc compounds) for broilers fed the cornsoybean diet. Zinc sulphate was used as the criterion of bioavailability.…”
Section: Enrichment Of Meat With Microelementsmentioning
confidence: 99%